An Economic Analysis of Ozone Control in California's San Joaquin Valley - Hong Jin Kim; Gloria E. Helfand; Richard E. Howitt (Journal of Agricultural and Resource Economics, 1998)
This study estimates the benefits to agricultural and human health of reducing ozone in the San Joaquin Valley of California, and the costs of ozone control. The San Joaquin Valley's highly valued crops suffer from high ozone levels. Federal and state primary ozone standards are based on health effects, not effects on other sectors, and do not consider costs of attaining the standards. The methods here allow comparison of both total and marginal benefits and costs. The results suggest that net gains can be achieved for the entire valley by reducing ozone below 1990 levels, although results vary by region.